Belgium : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2007)
This 2006 Article IV Consultation highlights that the economic upturn that started in mid-2005 in Belgium has remained on track. On the heels of a catch-up in private investment, the revival of private consumption and the cyclical expansion in neighboring countries have broadened the recovery to all sectors of the economy. Underlying inflation has been stable and broadly in line with the euro area average. Despite some real exchange rate appreciation and interest rate hikes, monetary conditions have remained accommodating. On other structural issues, the upward trend in employment rates is set to continue.